Studi Korelasi Antara Pendidikan dan Pelatihan (Diklat) Tutor PAUD dengan Peningkatan Kompetensi Mengajar - Sya'i, Syanjar; Rizka, M A; Gunawan, I Made (Jurnal Paedagogy, 2021)
The purpose of this study was to analyze the correlation between education and training (Diklat) of PAUD tutors with increasing teaching competence. This research method uses the correlational method. The sample in this study were 20 PAUD tutors at BPKBM NTB. The instruments used in this research are questionnaires and documentation. The analysis technique used is product moment correlation analysis. The results showed the arithmetic r value of 0.455 while the value of r in the table with a significance level of 5% and N = 20 was 0.444 (r count 0.455 > r table 0.444). This means that Ho is rejected while Ha is accepted. Based on the interpretation table of the correlation coefficient, it can be seen that the correlation r count is 0.455 including the medium category. The conclusion obtained from the results of this study is that there is a positive correlation between education and training (DIKLAT) with an increase in the teaching competence of PAUD tutors.